2003
DOI: 10.1016/s0006-3495(03)74798-5
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes, Disks, and Spherical Micelles: Aggregate Structure in Mixtures of Gel Phase Phosphatidylcholines and Poly(Ethylene Glycol)-Phospholipids

Abstract: Poly(ethylene glycol) (PEG) decorated lipid bilayers are widely used in biomembrane and pharmaceutical research. The success of PEG-lipid stabilized liposomes in drug delivery is one of the key factors for the interest in these polymer/lipid systems. From a more fundamental point of view, it is essential to understand the effect of the surface grafted polymers on the physical-chemical properties of the lipid bilayer. Herein we have used cryo-transmission electron microscopy and dynamic light scattering to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
189
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(209 citation statements)
references
References 28 publications
16
189
1
Order By: Relevance
“…From previous studies it appears that components, as well as environmental conditions, that increase the monolayer bending modulus and decrease the spontaneous curvature of the mixture promote the formation of discs [12]. As discussed before [10,12] formation of the discoidal micelles requires partial component segregation. For curvature reasons the PEG-lipids accumulate at the hemispherical disc edge whereas the bilayer forming lipids reside preferentially in the flat part of the disc.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…From previous studies it appears that components, as well as environmental conditions, that increase the monolayer bending modulus and decrease the spontaneous curvature of the mixture promote the formation of discs [12]. As discussed before [10,12] formation of the discoidal micelles requires partial component segregation. For curvature reasons the PEG-lipids accumulate at the hemispherical disc edge whereas the bilayer forming lipids reside preferentially in the flat part of the disc.…”
Section: Introductionmentioning
confidence: 71%
“…Their presence, however, may seriously influence the aggregate structure. High concentrations of PEG-lipids will, in most phospholipid/PEG-lipid mixtures, induce the formation of mixed spherical micelles [4][5][6][7][8][9][10][11]. Previous studies have shown that two fundamentally different types of mixed micellar aggregates may form at intermediate PEG-lipid to lipid ratios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the fraction of PEG2kBiotin present resulted in increased binding ( Figure 3B), however PEG2kBiotin at a concentration of 15% reduced the microbubble concentration by 30% as compared to a total PEG lipid concentration of 10%. PEG lipids at a high concentration have the potential to destabilize the microbubble lipid shell [39,40]. As a result, the concentration of PEG2k and PEG2kBiotin was 5% in all experiments.…”
Section: Peg2k/peg2kbiotin Ratio In Biotinylated Microbubble-the Molamentioning
confidence: 99%